Cash Waqf Linked Sukuk: Sharia Financial Innovation for Productive Waqf Management in Indonesia - Rahmani, Salma; Prasetyo, Yoyok (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
Productive waqf management in Indonesia faces challenges in innovation and optimizing the use of funds. Cash Waqf Linked Sukuk (CWLS), an innovative sharia financial instrument that integrates cash waqf with sukuk, appears as a potential solution. CWLS allows people to contribute through cash waqf which is then invested in sukuk, with the investment proceeds used for social projects such as infrastructure, health and education. This research aims to analyze the concepts, mechanisms and contracts implemented in CWLS, as well as evaluate their contribution to productive waqf management and their social impact in Indonesia. Using the literature study method, this research examines various primary and secondary data sources. The research results show that CWLS not only increases the productive use of waqf funds, but also provides a significant social impact through financing social and infrastructure projects. CWLS has proven to be an efficient solution in managing waqf and opens up new opportunities for economic empowerment of the people. However, challenges such as limited public understanding, the need for qualified human resources, and lack of digital access need to be addressed. This research concludes that CWLS has great potential to strengthen the waqf ecosystem and support sharia financial inclusion in Indonesia, with the right support from the government, sharia financial institutions and the community. Increased education and outreach efforts are needed to overcome these barriers and maximize the benefits of CWLS.